2019
DOI: 10.24052/jbrmr/v14is01/art-10
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the E- CRM (expected security and convenience of website design) on E- loyalty field study on commercial banks

Abstract: This study aimed to investigate the micro-linkages between electronic customer relationship management (E-CRM) and electronic loyalty of customers, through electronic banking satisfaction as a mediator variable. specifically, the neglected roles for expected security, convenience of website design. To achieve the objectives of the study, four basic hypotheses were formulated, it's were tested using preliminary data collected through the survey list, Data was collected by a convenience sample, the sample of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 34 publications
5
23
0
1
Order By: Relevance
“…Tariq, Jamil, Ahmad & Ramayah (2019) studied the relationship between the effectiveness of E-CRM (measured by interpersonal communication, perceived rewards and electronic direct mail) with customer loyalty and advocated that the customer tend to be loyal to their banks when they are equipped with the proper employment of E-CRM services. Rashwan, Mansi & Hassan (2019) also opined that appropriate implementation of E-CRM services (measured by expected security and convenience) will help the customers to transact more with their banks which will further lead to a profitable customer base, thereby increasing the financial performance of the banks. Sokmen & Bas (2019) investigated the impact of E-CRM measured by perceived transactions and rewards) on the loyalty of the customer in the context of the airlines industry and revealed that E-CRM technology positively leads to customer loyalty as customers are provided with personalized transactions and interactions which increases their satisfaction level, thus leading to customer loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Tariq, Jamil, Ahmad & Ramayah (2019) studied the relationship between the effectiveness of E-CRM (measured by interpersonal communication, perceived rewards and electronic direct mail) with customer loyalty and advocated that the customer tend to be loyal to their banks when they are equipped with the proper employment of E-CRM services. Rashwan, Mansi & Hassan (2019) also opined that appropriate implementation of E-CRM services (measured by expected security and convenience) will help the customers to transact more with their banks which will further lead to a profitable customer base, thereby increasing the financial performance of the banks. Sokmen & Bas (2019) investigated the impact of E-CRM measured by perceived transactions and rewards) on the loyalty of the customer in the context of the airlines industry and revealed that E-CRM technology positively leads to customer loyalty as customers are provided with personalized transactions and interactions which increases their satisfaction level, thus leading to customer loyalty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the customers are provided with the freedom of choosing their products and services, it increases their loyalty (Alhaiou et al, 2012). Loyal customers are more likely to stay and continue to engage in their bank's services whereas dissatisfied customers will switch to other banks' services (Rashwan et al, 2019). Customized products and/or services are defined as the "degree to which customers are free to customize their products and/or services that best suit their needs and wants" (Feinberg, Kadam, Hokama & Kim, 2002).…”
Section: Research Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations